The Effect of Physical Activity on Physical Fitness in Early Childhood - Santri, Aski Ratna; Anggita, Gustiana Mega (Sports Medicine Curiosity Journal, 2023)
In the era of digital life, it provides convenience in various aspects of life. Children familiar with gadgets tend to prefer playing with them or choosing to watch. This raises sedentary behaviour in children so that children do less physical activity and can trigger other diseases such as obesity, type 2 diabetes, respiratory, psychological, etc. This research is a literature study that discusses the effects of physical activity on children's health. The primary literature consists of 15 national and international journals. The results showed that physical activity has a positive effect in terms of health and academics.